Delay In Procurement Of Ship Parts Owned By Pt Sumberbumi Global Niaga In Consumer Legal Protection - Agung Kwartama; Titis Ari Wibowo; Lie Adek (International Journal of Technology and Education Research, 2024)
This research analyzes the impact of delays in spare parts procurement on PT Sumberbumi Global Niaga's ship operations at PT Sumberbumi Global Niaga, one of the most important shipping companies in Indonesia, especially specializing in ship ownership and transshipment services. Company vessels are used in time charter voyages because the vessels are leased to shippers for individual voyages. Disruptions to spare parts procurement are notorious for their impact on the operating efficiency and effectiveness of these vessels, resulting in lower productivity, higher costs and potential safety hazards. The purpose of this research is to explore the reasons and impact of delays in spare parts procurement on PT Sumberbumi Global Niaga's fleet operations, such as ship downtime, preventive maintenance schedules, and general business results. It is hoped that the results obtained from this research will provide useful information for companies to improve the spare parts procurement process as well as reduce delays and improve operational performance.